Komunikasi Non Verbal dalam Animasi Tekotok dalam Episode Bapak Atitude Nol - Maulidah, Nur Hasyim (Komunika : Jurnal Ilmiah Komunikasi, 2024)
This research focuses on non-verbal communication exhibited by an annoying older man performing various activities, earning him the nickname Mr. Zero Attitude in the Tekotok animation. Non-verbal communication is a crucial element in responding to messages, either directly or indirectly. In this episode, verbal communication plays a vital role in depicting the main character and the interactions among the characters. The dialogue used reflects cultural values, societal norms, and social criticism relevant to daily life. The language also showcases the uniqueness of local culture, including accents, word choices, and distinctive humor that is easily relatable to the audience. The research employs a qualitative method using an observational approach through YouTube as a platform for gathering primary and secondary data. The sources for this research include YouTube, journals, and books. The purpose of this study is to understand how Mr. Zero Attitude employs non-verbal communication in his interactions with others. The problem addressed in this research is the non-verbal communication displayed by Mr. Zero Attitude, which does not align with the social norms of the community.